Supplementation and inhibition of nitric oxide synthesis influences bacterial transit time during bacterial translocation in rats - Samel, Stephan Tim; Keese, Michael; Lanig, Sybille; Groove-Kleczka, Martha; Gretz, Norbert; Hafner, Mathias; Sturm, Jörg; Post, Stefan (Shock, 2003)
In the obstructed gut, nitric oxide (NO) may influence intestinal barrier function and translocation of bacteria. By using a novel experimental approach, we investigated the effect of supplementation and inhibition of NO synthesis on the time interval necessary for translocation of green fluorescent protein-transfected Escherichia coli (GFP-uv E. coli) in a rat model of small bowel obstruction. In anesthetized Wistar rats, 4 x 108 GFP-uv E. coli were administered into a reservoir of terminal ileum formed by ligature. Animals were randomized to receive either i.v. arginine (10 mg/kg), aminoguanidine (300 mg/kg), l-NAME (25 mg/kg), or saline (control). Translocation of GFP-uv E. coli was assessed using intravital video microscopy. Minimal transit time of translocation was measured as time from injection of GFP-uv E. coli into the gut lumen until bacteria were observed in the lamina submucosa and as time from injection of bacteria into the gut lumen until bacteria were observed in the lamina muscularis propria. Minimal transit times were expressed as mean ± SD. Bacterial translocation into the submucosa and muscularis propria took 36 ± 7 min and 81 ± 9 min, respectively in control animals receiving saline. Aminoguanidine and l-NAME caused a marked delay of minimal transit time into the submucosa (63 ± 5 min and 61 ± 7 min, respectively;P < 0.05). Arginine significantly accelerated bacterial translocation into the muscularis propria (61 ± 9 min, P < 0.05). GFP-uv E. coli were detected on frozen sections of small bowel, mesentery, liver, and spleen 2 h after GFP-uv E. coli administration in all animals. A marked upregulation of inducible NO synthase (NOS) in the obstructed bowel segment was demonstrated on immunohistochemistry. The assessment of a newly defined parameter, minimal bacterial transit time, may serve as an additional functional aspect of intestinal barrier function for pathophysiological and pharmacological studies. Aminoguanidine, l-NAME, and arginine were effective in influencing minimal transit time of E. coli during small bowel obstruction.
Gesehen am 22.06.2022